FACTORS INFLUENCING VISITORS SHOPPING AT CIPULIR MARKET, SOUTH JAKARTA - Heny, henyratnaningtyas; Ingkadijaya, Rahmat; Asmaniati, Fetty; Emier Osman, Ismeth; Amrullah, Amrullah (Jurnal Mebis, 2024)
This research aims to determine the influence of product variations and prices on purchasing decisions at Cipulir Market. This type of research is quantitative descriptive with multiple regression analysis methods. The population of this research is all visitors who come to Cipulir Market. The research sample consisted of 100 respondents. Data were collected by distributing questionnaires with a Likert scale from 1 to 5. Sampling used accidental sampling. The partial research results show that product variations and prices significantly affect purchasing decisions at Cipulir Market. The variety of textiles and finished goods products significantly influence buying decisions at Cipulir Market because it reflects the diversity of consumer tastes and provides more comprehensive options for buyers to choose according to their preferences. Price significantly influences purchasing decisions at Cipulir Market because consumers generally access this market from lower to middle economic levels. Competitive and affordable prices are the main factors influencing purchasing decisions in this market. It is hoped that traders at Cipulir Market will be able to increase sales, strengthen the attractiveness of their stands, and build customer trust through strategies that understand customer needs.